2011
DOI: 10.3892/etm.2011.256
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of expression of CCN family members Cyr61, CTGF and NOV in human acute and chronic wounds

Abstract: Abstract. The CCN family is a group of extremely cysteinerich proteins that are found within the extracellular matrix and are comprised of cysteine-rich 61 (Cyr61/CCN1), connective tissue growth factor (CTGF/CCN 2) and nephroblastoma overexpressed (NOV/CCN3). Collectively, these proteins stimulate mitosis, adhesion, apoptosis, extracellular matrix production, growth arrest and migration, and regulate angiogenesis, tumour growth, placentation, implantation, embryogenesis and endochondral ossification. Despite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“… 20 In another example, CCN1 has been reported previously to promote inflammation and wound repair. 38 - 40 In these studies, Bai et al demonstrated that a high dose of CCN1 (10 μg/ml) treatment leads to an up-regulation of pro-inflammatory cytokine/chemokine mRNAs in macrophages. 38 CCN1 supports the adhesion of macrophages, activates NF-κB mediated transcription, and induces pro-inflammatory cytokines which are generated by classically activated M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In another example, CCN1 has been reported previously to promote inflammation and wound repair. 38 - 40 In these studies, Bai et al demonstrated that a high dose of CCN1 (10 μg/ml) treatment leads to an up-regulation of pro-inflammatory cytokine/chemokine mRNAs in macrophages. 38 CCN1 supports the adhesion of macrophages, activates NF-κB mediated transcription, and induces pro-inflammatory cytokines which are generated by classically activated M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The connective tissue growth factor/cysteine-rich 61/nephroblastoma overexpressed (CCN) family comprises six highly conserved cysteine rich proteins. Mounting evidence suggests the critical roles of CCN family in various cell processes including proliferation and adhesion, homeostasis, osteoblast differentiation, wound repair, inflammation, fibrosis and tumorigenesis ( 7 9 ). Of these members, connective tissue growth factor (CTGF)/CCN2 acts as an ECM protein and is associated with wound healing and scar formation ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…142 In chronic human wounds, the expression of CCN1/Cyr61 is increased, and CCN2/CTGF is significantly reduced compared with normally healing wounds. 149 The excessive expression of CCN1/ Cyr61 may result in premature a 6 b 1 -integrinmediated myofibroblast senescence that is associated with early down-regulation of ECM (e.g., collagen) production, up-regulation of matrix-degrading proteases, and ongoing breakdown of the granulation tissue before the re-epithelialization is completed, contributing to the wound chronicity. 142,146 In hypertrophic scars, myofibroblasts persist and 778 they continue to produce excessive matrix possibly because of a reversed CCN1/ Cyr61 and CCN2/CTGF balance.…”
Section: Integrins Are Essential For Angiogenesismentioning
confidence: 99%